Sosial Media dan Gaya Hidup Hedonisme Terhadap Perilaku Konsumtif pada Karyawan Muda di Kota Semarang - Pratiwi, Ade Ayu; Yuliana, Rahmi; Hamdani, Muliawan (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2024)
This study aims to analyze the influence of social media use and hedonism lifestyle on the consumptive behavior of young employees in Semarang City. The sample in this study was 150 respondents taken by purposive sampling. The data collection technique in this study used a questionnaire with the help of Google Form. The analytical method used in this research is multiple linear regression analysis using the SPSS version 26 program as a data processing tool. The results of this study indicate that social media and hedonism lifestyle have a positive and significant effect on the consumptive behavior of young employees in Semarang City.